2021
DOI: 10.1080/10833196.2021.1988816
|View full text |Cite
|
Sign up to set email alerts
|

Exercise booster sessions as a mean to maintain the effect of an exercise-intervention - A systematic review

Abstract: Exercise booster sessions as a mean to maintain the effect of an exerciseintervention -A Systematic ReviewBackground: Exercise is known to have many beneficial effects. Nevertheless, long-term adherence remains a challenge. A concept suggested to attend this problem is Exercise Booster Sessions (EBS). However, the current knowledge on EBS is limited.Objectives: This systematic review aimed to summarize and synthesize 1) the reported effects of EBS on physical function, pain, quality-of-life and societal costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Should a patient experience any unsatisfactory effects, the patient may crossover to the TSA group, and the reasons for crossover will be registered. If patients choose to continue in the exercise group, they will receive 4 individual physiotherapist-supervised exercise booster sessions at 4, 6, 8, and 10 months after initiating the exercise program as a means to maintain the effect (15).…”
Section: Exercise Groupmentioning
confidence: 99%
“…Should a patient experience any unsatisfactory effects, the patient may crossover to the TSA group, and the reasons for crossover will be registered. If patients choose to continue in the exercise group, they will receive 4 individual physiotherapist-supervised exercise booster sessions at 4, 6, 8, and 10 months after initiating the exercise program as a means to maintain the effect (15).…”
Section: Exercise Groupmentioning
confidence: 99%
“…It can be a cost-effective solution to replace face-to-face exercise (regardless of where the patients live) 25 41. Previous studies have shown adherence to exercise is lower in TR (especially over time), and also a significant reduction in the clinical effects of exercise occurs in the follow-up period 44 45. Therefore, they recommend that patients in a follow-up period receive ‘exercise booster sessions (EBSs)’ in the delivery of exercises, facilitating longer-term maintenance of beneficial effects 44 46–48.…”
Section: Introductionmentioning
confidence: 99%
“…One such intervention is exercise booster sessions (EBS), which is training sessions provided regularly throughout the follow-up period to sustain effects of the preceding exercise intervention and to motivate participants to continue exercising after the initial supervised training sessions have ended. 22 In knee OA, there is some evidence to suggest that EBS may improve pain and self-reported disability 23 and lead to cost savings for the healthcare system. 24 Prior studies investigating EBS in patients with hip OA did not provide treatment arms with an identical initial exercise intervention, and thus, cannot determine the effectiveness of EBS for maintaining the effects of an initial intervention.…”
Section: Introductionmentioning
confidence: 99%
“…This warrants research in interventions aimed at improving long-term exercise adherence and thereby prolonging the initial effects. One such intervention is exercise booster sessions (EBS), which is training sessions provided regularly throughout the follow-up period to sustain effects of the preceding exercise intervention and to motivate participants to continue exercising after the initial supervised training sessions have ended 22. In knee OA, there is some evidence to suggest that EBS may improve pain and self-reported disability23 and lead to cost savings for the healthcare system 24.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation